Simplification of Patient-Reported Outcome Measures in Oncology: A Narrative Review - Shahad Al-Mukhtar; Mohammed Aladul; Manal Mohammed Younus; Dian Salih (University of Mosul, 2024)
Background: Patient-reported outcomes (PROs) are reports provided by patients themselves detailing their medical health state or behavior related to an illness or medication use, without any interpretation by healthcare professionals. PROs are used to evaluate health status that cannot be quantified through tangible measures, for primary outcomes such as pain severity, and secondary outcomes such as quality of life. Patient-reported outcome measures (PROMs) are instruments or methods developed by professionals to assess data on PROs directly provided by patients during reporting procedures. In the oncology field, they are important to determine the impact of cancer and chemotherapy on patient's physical symptoms, mental well-being, and social functioning. The health system turned towards using PROMs as tools for remote monitoring, conducting visits when needed, and alerting stakeholders at the right time. Aim: To describe the uses and types of PROMs in use in clinical practice and the simplified PROMs that have been developed in oncology. Conclusion: PROMs are widely used in oncology for data collection. It became necessary to simplify measures by using patients' language, downsizing content, and promoting electronic PROMs through technological programs.